\(x+y=2\Leftrightarrow\left(x+y\right)^2=4\)
\(\Leftrightarrow x^2+y^2+2xy=4\)
\(\Leftrightarrow2xy=-6\)
\(\Leftrightarrow xy=-3\)
\(x^3+y^3=\left(x+y\right)\left(x^2-xy+y^2\right)\)
\(=2.13=26\)
Vậy...
x2 + 2xy +y2= ( x+y)2
=> ( x+y)2- 2xy = x2 + y2=10 (1)
Mà x+ y= 2 (2)
Từ (1) và (2) suy ra xy= -3 (3)
Lại có: x3 + y3= (x + y)3 -3xy(x+y)(4)
Từ (2), (3), (4) suy ra:
x3+ y3= 26
ta có : \(x^2+y^2=10\Leftrightarrow\left(x+y\right)^2-2xy=10\Leftrightarrow2^2-2xy=10\)
\(\Leftrightarrow2xy=-6\Leftrightarrow xy=-3\)
thay \(x+y=2vàxy=-3\) vào \(x^3+y^3\)
ta có : \(x^3+y^3=\left(x+y\right)^3-3xy\left(x+y\right)=2^3-3.\left(-3\right)\left(2\right)=8+18=26\)
vậy \(x^3+y^3=26\) khi \(x+y=2vàx^2+y^2=10\)
x+y=2⇔(x+y)2=4x+y=2⇔(x+y)2=4
⇔x2+y2+2xy=4⇔x2+y2+2xy=4
⇔2xy=−6⇔2xy=−6
⇔xy=−3⇔xy=−3
x3+y3=(x+y)(x2−xy+y2)x3+y3=(x+y)(x2−xy+y2)
=2.13=26=2.13=26
Vậy...